2017
DOI: 10.1186/s40360-017-0134-9
|View full text |Cite
|
Sign up to set email alerts
|

Drug adherence for antihypertensive medications and its determinants among adult hypertensive patients attending in chronic clinics of referral hospitals in Northwest Ethiopia

Abstract: BackgroundAdherence to prescribed medication is an imperative issue which can be directly linked with the management of chronic diseases like hypertension; failure to adhere can affect the effectiveness of medication as well as the efficiency of the health care system. There is scarcity of information regarding the level of drug adherence for antihypertensive medications and its determinants in Ethiopia, particularly in the study area. Therefore, the aim of this study was to assess adherence level and its dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
87
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(109 citation statements)
references
References 33 publications
9
87
3
1
Order By: Relevance
“…Moreover, participants who purchased medications by themselves were less likely to adhere to their medications than participants who get their mediations freely. This is similar with a study done in northwest Ethiopia which showed higher odds of adherence to antihypertensive medications in respondents who had got the medication/s free of charge or with low cost as compared to those who had got the medication/s with high cost [ 34 ]. This might be attributable to the economic constraint of the former participants.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, participants who purchased medications by themselves were less likely to adhere to their medications than participants who get their mediations freely. This is similar with a study done in northwest Ethiopia which showed higher odds of adherence to antihypertensive medications in respondents who had got the medication/s free of charge or with low cost as compared to those who had got the medication/s with high cost [ 34 ]. This might be attributable to the economic constraint of the former participants.…”
Section: Discussionsupporting
confidence: 90%
“…Self-reported adherence in the walkway model was better than in health facility and weekend clinics. The selfreported adherence in this study is much higher than shown in other studies in Africa: 53.8% in Korogocho slum, Nairobi [24], 57.2% in Nigeria [25] and 67.2% in North-west Ethiopia [26]; it is also higher than in Pakistan (76.6%) [27] and Sunderland (79%) [28]. The difference in results may be due to sociodemographic characteristics, self-reported adherence or models of care.…”
Section: Discussioncontrasting
confidence: 85%
“…In contrast to our findings, there was no significant association between number of medications taken and adherence level in other national studies [9,21]. In a third international study conducted in northwest Ethiopia, Mekonnen et al [26] showed that participants who had no comorbidity were four times more likely to adhere to antihypertensive medications than their counterparts.…”
Section: Discussioncontrasting
confidence: 99%